Peer-to-peer energy trading system using IoT and a low-computation blockchain network - Ncube, Tyron (Rhodes University, Faculty of Science, Department of Computer Science)
The use of renewable energy is increasing every year as it is seen as a viable and sustain- able long-term alternative to fossil-based sources of power. Emerging technologies are being merged with existing renewable energy systems to address some of the challenges associated with renewable energy, such as reliability and limited storage facilities for the generated energy. The Internet of Things (IoT) has made it possible for consumers to make money by selling off excess energy back to the utility company through smart grids that allow bi-directional communication between the consumer and the utility company. The major drawback of this is that the utility company still plays a central role in this setup as they are the only buyer of this excess energy generated from renewable energy sources. This research intends to use blockchain technology by leveraging its decentralized architecture to enable other individuals to be able to purchase this excess energy. Blockchain technology is first explained in detail, and its main features, such as consensus mechanisms, are examined. This evaluation of blockchain technology gives rise to some design questions that are taken into consideration to create a low-energy, low-computation Ethereum-based blockchain network that is the foundation for a peer-to-peer energy trading system. The peer-to-peer energy trading system makes use of smart meters to collect data about energy usage and gives users a web-based interface where they can transact with each other. A smart contract is also designed to facilitate payments for transactions. Lastly, the system is tested by carrying out transactions and transferring energy from one node in the system to another.
Keywords: Blockchains (Databases); Internet of things; Renewable energy sources; Smart power grids; Peer-to-peer architecture (Computer networks); Energy trading system